Performance analysis of machine learning algorithms in resume recommendation systems - Hasan, Ibteaz; Chakraborty, Ratnadeep; Alam, Md. Ashraful (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.